Inter-Comparison of the Spatial Distribution of Methane in the Water Column From Seafloor Emissions at Two Sites in the Western Black Sea Using a Multi-Technique Approach - Grilli, Roberto; Birot, Dominique; Schumacher, Mia; Paris, Jean-Daniel; Blouzon, Camille; Donval, Jean Pierre; Guyader, Vivien; Leau, Helene; Giunta, Thomas; Delmotte, Marc; Radulescu, Vlad; Balan, Sorin; et al. (Frontiers in Earth Science, 2021)
Understanding the dynamics and fate of methane (CH4) release from oceanic seepages from margins and shelves into the water column, and quantifying the budget of its total discharge at different spatial and temporal scales, currently represents a major scientific undertaking. The assessment of methane’s sensitivity to global warming, its injection into the atmosphere and its role in the oceanic carbon cycle are only a few of the potential research fields. Previous works on the fate of methane escaping from the seafloor underlined the challenge in both, estimating its concentration distribution and identifying gradients. Here, accuracy and precision are prerequisites to a reliable analysis. During the Envri+ Methane Cruise onboard the R/V Mare Nigrum in April 2019, acoustic surveys, continuous in-situ measurements from a membrane inlet laser spectrometer (MILS) and a commercial methane sensor (METS) from Franatech GmbH, as well as discrete water sampling followed by onshore laboratory analysis were conducted and will be discussed here. The results highlight the challenge to obtain reliable and precise measurements of dissolved gases due to instrumental limitations, as well as the complexity of mapping the seepage area due to large spatial and temporal variability of the water mass composition. In-situ techniques and acoustic data revealed a good qualitative matching of the spatial distribution of methane emissions. The accuracy of the in situ sensors to measure dissolved methane concentration was then assessed by a quantitative comparison with standard onshore methods. From vertical profiles (from both continuous and discrete measurements), a dissolved methane profile following an expected exponential dissolution function was observed at both sites. At the deeper site ( 120 m water depth), dissolved methane transported by the bubbles may reach up to 45 m from the seafloor, while at the shallower site ( 55 m water depth) CH4 concentrations at the sea surface were four times higher than the expected equilibrium concentrations. High spatial resolution surface data also support this hypothesis, suggesting a transfer of CH4 from the sea to the atmosphere at shallower depths. Well localized methane enriched waters were found near the surface but they appear decoupled with the location of the seafloor seepages,